Interfirm knowledge management through a web-based benchlearning system. (18th December 2008) - Lemmergaard, Jeanette
The survival of firms in an increasingly competitive and global market depends on adequate management of human resources. Adequate management necessitates evaluation of human resources, and in order to obtain organisational learning and gain from knowledge spillovers, implementing a benchlearning tool containing both measurement and valuation is suggested. Such benchlearning tool, however, must facilitate both the process of measuring and of evaluating, and it must communicate the value added from human resources practices. A knowledge-creating and knowledge-sharing web-based IT-benchlearning tool is presented. The system supports organisational learning through interorganisational knowledge sharing. The portal is an interactive IT architecture that supports firms in exchanging knowledge. The architecture is novel in its approach of facilitating benchlearning across industry boundaries and within a soft area (i.e., human resource practices and processes). Besides supporting interfirm knowledge creation and sharing, the tool assists managers in more efficient and qualitative decision-making.